2013
DOI: 10.1186/1471-2393-13-45
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of pregnant women about birth defects

Abstract: BackgroundOccurrence of birth defects (BD) remains an important public health issue. Inadequate knowledge about the defects among prospective mothers could result in delayed interventions. The study determined the knowledge of BD among pregnant women in relation to their socio-demographic profile.MethodFour hundred and forty-three (443) pregnant women gave their consent to participate in this study. A researcher-administered questionnaire was used to obtain information on socio-demographic characteristics from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 6 publications
4
32
5
Order By: Relevance
“…This is imperative for women to have a positive attitude in general toward medicines that is acceptable. Among the women who had an abnormal child, none considered medications as the cause; rather they attributed it to heredity, a curse, or something supernatural, since it is believed by the majority of African women that birth defects are attributed to divine factors (23). This is similar to a Saudi Arabia study that indicated that women believe that drugs were not the reason for congenital abnormality (15).…”
Section: Discussionmentioning
confidence: 66%
“…This is imperative for women to have a positive attitude in general toward medicines that is acceptable. Among the women who had an abnormal child, none considered medications as the cause; rather they attributed it to heredity, a curse, or something supernatural, since it is believed by the majority of African women that birth defects are attributed to divine factors (23). This is similar to a Saudi Arabia study that indicated that women believe that drugs were not the reason for congenital abnormality (15).…”
Section: Discussionmentioning
confidence: 66%
“…The same were reported in several studies. (9)(10)(11) Our results reported that viral infections during pregnancy were mentioned as a risk factor for CA by participants. The same was recorded by some studies.…”
Section: Discussionmentioning
confidence: 78%
“…(10,11) However, good knowledge was reported among 20.1% of participants in the present study whereas much higher level of knowledge was reported by other studies. (9,11) This may be due to different socio-demographic characteristics of study participants (illiterate rural residents). On the other hand, Sidhu et al (12) reported that only 4.5% of their participants had good knowledge regarding congenital malformations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior research has identified a wide array about causal beliefs related to birth defects, including using drugs and alcohol (Cohen et al 1998;Griffiths and Kuppermann 2008), smoking (Bello et al 2013), maternal impression (Castro 1995;Callister and Vega 1998;Cohen et al 1998;Snow 1983), eating certain foods (Cheng 1990;Dryden 1990), heredity (Cohen et al 1998;Dryden 1990;Griffiths and Kuppermann 2008;Nelson et al 2009;Ojofeitimi and Elegbe 1984), God's will (Ojofeitimi and Elegbe 1984), lunar or solar eclipses (Callister and Vega 1998;Snow 1983), intake of medications or vaccines (Griffiths and Kuppermann 2008;Mazzotta et al 1999;Sanz et al 2001), parental punishment or karma (Cheng 1990;Ojofeitimi and Elegbe 1984;Snow 1983;Viste 2007), advanced maternal age (Bello et al 2013) and receiving x-rays during pregnancy (Bentur et al 1991). However, these studies are largely ethnographic, focusing on unique, traditional cultures or very specific ethnic populations, often emphasizing folk beliefs and supernatural attributions.…”
Section: Introductionmentioning
confidence: 99%